2019
DOI: 10.1001/jamanetworkopen.2019.9126
|View full text |Cite
|
Sign up to set email alerts
|

Association of Timing of Adjuvant Therapy With Survival in Patients With Resected Stage I to II Pancreatic Cancer

Abstract: Key Points Question Is the timing of adjuvant therapy in resected pancreatic cancer associated with better survival? Findings This cohort study of 7548 patients with stage I to II pancreatic cancer in the National Cancer Database suggested improved survival when adjuvant therapy was initiated 28 to 59 days after surgery. Patients who recovered slowly from surgery still benefited from delayed adjuvant therapy initiated more than 12 weeks after the procedure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 52 publications
1
36
2
Order By: Relevance
“…We retrospectively analyzed the duration of adjuvant treatment grouped into three categories (without or <2 months, 2-4 months, and 4-6 months) and found that a longer duration conferred benefit to RPC patients, demonstrating the adequate adjuvant course for the high recurrence risk population, and may present a potentially promising treatment option of consolidation therapy in pancreatic cancer patients. Most of the patients in our study initiated adjuvant therapy within eight weeks postoperatively according to the current consensus (50), and previous results showed that patients still benefit from adjuvant therapy started more than 12 weeks after surgical resection (51). From 2013, eligible patients were continuously recruited, and our study may present as one of the largest sample sizes published in pancreatic cancer to date.…”
Section: Discussionmentioning
confidence: 94%
“…We retrospectively analyzed the duration of adjuvant treatment grouped into three categories (without or <2 months, 2-4 months, and 4-6 months) and found that a longer duration conferred benefit to RPC patients, demonstrating the adequate adjuvant course for the high recurrence risk population, and may present a potentially promising treatment option of consolidation therapy in pancreatic cancer patients. Most of the patients in our study initiated adjuvant therapy within eight weeks postoperatively according to the current consensus (50), and previous results showed that patients still benefit from adjuvant therapy started more than 12 weeks after surgical resection (51). From 2013, eligible patients were continuously recruited, and our study may present as one of the largest sample sizes published in pancreatic cancer to date.…”
Section: Discussionmentioning
confidence: 94%
“…This trend is concerning as research suggests that the timing of chemotherapy administration affects pancreatic cancer outcomes. 6 Contributing factors likely include the temporary freeze of clinical trial enrollment at our large academic center during the pandemic and subsequent patient preference to undergo standard of care chemotherapy options closer to home and in the community.…”
Section: Discussionmentioning
confidence: 99%
“…However, 50% of patients may never commence adjuvant chemotherapy due to post-operative complications or poor performance status, and a proportion of patients do not complete the intended course [30,31]. Additionally, with increasing time from surgery to chemotherapy initiation, there may be a reduction in the survival benefit [32], and this is of particular relevance in patients who do not complete the full planned course of adjuvant chemotherapy [33]. These factors, along with other theoretical advantages such as earlier treatment of micro-metastatic disease, the potential to downstage tumors with improved R0 resection rates, and the opportunity to study disease biology prior to subjecting patients to major surgery, led to increased interest in neo-adjuvant treatment strategies.…”
Section: Guidelinesmentioning
confidence: 99%